La baie des anges - Legrand, Michel 1932-2019 (Arte Vidéo [u.a.], 2008)
A hypnotic tale of love at the roulette wheel as a compulsive gambler falls in love with a bank clerk on holiday
Orig.: F 1962
16/9 compatible 4/3. - Filmlaufzeit 79 min.
Enth. Extras: Le film vu par Mathieu Demy ; a propos du film, texte de Jean-Pierre Berthomé, lu par Mathieu Demy ...
Keywords: Gambling / Drama; Man-woman relationships / Drama; Motion pictures / France; Film; Gambling -- Drama; Man-woman relationships -- Drama; Motion pictures -- France; Frankreich; Feature films